Fostering Teamwork through Design Thinking: Evidence from a Multi-Actor Perspective - Sharon Guaman-Quintanilla; Patricia Everaert; Katherine Chiluiza; Martin Valcke (MDPI AG, 2022)
This study examines the effects of a design thinking intervention on first-year students' teamwork skills from a multi-actor perspective. A design thinking course was evaluated throughout a semester. Six-hundred-and-forty university students participated, guided by twenty-six facilitators. The students received in-class training and worked in multi-disciplinary teams to develop a solution for a real-life problem. In this quasi-experimental study, data were collected twice: in the middle (t1), and at the end (t2) of the course. Each time, students were rated by their teammates, themselves, and the course facilitator, using a rubric to map teamwork skills. The results show a significant improvement in teamwork skills, as consistently observed in the three ratings. The results also show a significant effect of sex on the improvement over time. Female students showed more considerable progress than male students. This study addresses researchers' demands regarding the lack of robust evidence to assess the impact of design thinking in higher education settings. Furthermore, building on the data from a large sample size and an intervention designed in a replicable way, this study contributes to the available empirical evidence that helps one to adopt and implement design thinking in universities to develop essential skills, such as teamwork.